Bacterial community composition of the gut microbiota of Cylindroiulus fulviceps (diplopoda) as revealed by molecular fingerprinting and cloning - Knapp, B. A; Seeber, J; Rief, A; Meyer, E; Insam, H (Folia microbiologica, 2010)
Bacterial clone libraries of the gut microbiota of nurtured and starved Cylindroiulus fulviceps specimens displayed the predominance of the phyla Bacteroidetes (55 and 37 %, respectively) and Proteobacteria (40 and 35 %, respectively) and a high similarity to bacteria previously detected in the intestinal tract of termites and beetles, which are known to harbor symbiotic bacteria essential for digestive activity. Bacterial isolates were dominated by Proteobacteria (74 %), followed by members of the phyla Actinobacteria, Firmicutes and Bacteroidetes. PCR-DGGE fingerprints of the gut samples showed that intestinal bacteria were affected by starvation, although the change was not significant.
Keywords: Animals; Cloning, Molecular; gastrointestinální trakt; metagenom; sekvenční analýza DNA; Metagenome; členovci; financování organizované; Gastrointestinal Tract; zvířata; Bacteroidetes; Actinobacteria; DNA Fingerprinting; Sequence Analysis, DNA; molekulární sekvence - údaje; DNA bakterií; Financing, Organized; Electrophoresis, Agar Gel; RNA, Ribosomal, 16S; bakteriologické techniky; Phylogeny; DNA fingerprinting; Arthropods; ekosystém; fylogeneze; Ecosystem; kultivační média; RNA ribozomální 16S; Molecular Sequence Data; Bacteriological Techniques; elektroforéza v agarovém gelu; Culture Media; Bacteria; DNA, Bacterial; klonování DNA; Proteobacteria